1995
DOI: 10.1182/blood.v85.9.2546.bloodjournal8592546
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the p53 and ras genes in childhood t(1;19)-acute lymphoblastic leukemia

Abstract: We have investigated the alterations of p53 and ras genes including H-, K-, and N-ras genes in 22 acute lymphoblastic leukemia (ALL) cases and five cell lines carrying t(1;19) by use of polymerase chain reaction (PCR)-single-strand conformation polymorphism (SSCP) analysis and direct sequencing. The mutations of the p53 gene were found in 2 of 20 t(1;19)-ALL cases at diagnosis (10%), all of 4 cases at relapse (100%), and 4 of the 5 cell lines (80%). Four of the five patients who died had missense mutations at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 0 publications
0
22
1
Order By: Relevance
“…Bone marrow or peripheral-blood (PB) specimens from 261 patients with hematological malignancies were collected from several hospitals in Japan. Twenty-two patients with de novo JMML, 17 with MDS, 85 with AML, 5 with T-ALL, 90 with B-precursor ALL and 42 with infant leukemia (6 with AML, 35 with ALL, and 1 with mixedlineage leukemia) were included (Kawamura et al, 1995;Sheng et al, 1997;Taketani et al, 2004). All these patients were diagnosed according to the French-American-British (FAB) classification system.…”
Section: Patients and Healthy Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow or peripheral-blood (PB) specimens from 261 patients with hematological malignancies were collected from several hospitals in Japan. Twenty-two patients with de novo JMML, 17 with MDS, 85 with AML, 5 with T-ALL, 90 with B-precursor ALL and 42 with infant leukemia (6 with AML, 35 with ALL, and 1 with mixedlineage leukemia) were included (Kawamura et al, 1995;Sheng et al, 1997;Taketani et al, 2004). All these patients were diagnosed according to the French-American-British (FAB) classification system.…”
Section: Patients and Healthy Controlsmentioning
confidence: 99%
“…We also screened JMML samples and all the cell lines and fresh tumors of RMS for NRAS, KRAS, and HRAS mutations in order to investigate the frequency of RAS mutations in JMML and RMS. Because it has been shown that all RAS gene mutations are localized in exons 1 and 2, PCR was carried out to amplify exons 1 and 2 of each gene, using the primers published previously (Kawamura et al, 1995;Sheng et al, 1997), followed by direct sequencing analyses.…”
Section: Mutational Analyses Of Rasmentioning
confidence: 99%
“…Kawamura et al found that one of 22 t(1;19) ALL children (4.5%) had NRAS mutations 22. Urbano-Ispizua et al reported that RAS mutations were detected in only one out of 26 (3.8%) patients with BCR-ABL1 ALL 23.…”
mentioning
confidence: 99%
“…6 Mutations of TP53 have been found in 2% of children at diagnosis of ALL, 7 but in 11%-28% after relapse, and are associated with lower OS, lower EFS, and higher RR, 8 indicating involvement in progression to more aggressive disease. 7,[9][10][11][12][13][14] We have previously shown an increased expression of p53 protein in children with myeloid leukemias, who relapse after HSCT. 15,16 The aim of this study was to investigate, by IHC, if alterations in the expression of p53 could be an additional prognostic marker for relapse after HSCT in pediatric ALL patients and thereby may help guiding in preemptive immunotherapy.…”
Section: Backg Rou N Dmentioning
confidence: 99%